1992
DOI: 10.1002/jsfa.2740590220
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the shell of apricot seeds

Abstract: Abstract:The chemical composition of the seed shell of the apricot (Prunus armeniaca) were investigated. Acid and neutral detergent fibres (ADF and NDF) and their fractions-hemicellulose, cellulose and lignin-were determined. The NDF content was about 920 g kg-' DM. The concentrations of oils, soluble sugars, pectins, polyphenolic compounds, proteins and mineral elements were also determined. None of these fractions was present at levels higher than 25 g kg-' DM. Essential amino acids comprised 3 8 4 1 % of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
2
12
2
Order By: Relevance
“…Overall, the total extractive content (1.82% based on OD APS) was higher than reported by Yeganeh et al (0.41% [23]) but lower than other results reported earlier: in accordance with Wei et al [22], APS contain 5.2% extractives while oil and polyphenolic compounds are present in the amount of 1.6%-2.2% and 0.74%-0.9% respectively in accordance with the results of Cañellas et al [12]. The low solubility of APS in cold and hot water indicates a minute amount of water-soluble carbohydrates, such as free sugars, glycosides, and starch.…”
Section: Chemical Composition Of Apssupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, the total extractive content (1.82% based on OD APS) was higher than reported by Yeganeh et al (0.41% [23]) but lower than other results reported earlier: in accordance with Wei et al [22], APS contain 5.2% extractives while oil and polyphenolic compounds are present in the amount of 1.6%-2.2% and 0.74%-0.9% respectively in accordance with the results of Cañellas et al [12]. The low solubility of APS in cold and hot water indicates a minute amount of water-soluble carbohydrates, such as free sugars, glycosides, and starch.…”
Section: Chemical Composition Of Apssupporting
confidence: 89%
“…Relatively low ash content (0.55%) determined in this study was lower than found by Cañellas et al (1.67% [12]) but between the values reported by other research groups (0.17% [22]; 0.2% [10,11]; 0.3% [23]; 0.78% [9]; 1.0% [24]). The ash content of apricot pit shells appears to be less, on average, than recorded for other fruit stones, seeds, and nut shells (nut shells: 1.2%-3.8%; almond shells: 1.54%-2.3%; cherry stones: 0.9%; grape seeds: 2.5% [10,11]), demonstrating benefits of using apricot pit shells for combustion, pyrolysis, or carbonization.…”
Section: Chemical Composition Of Apscontrasting
confidence: 73%
See 2 more Smart Citations
“…Potassium (2.44g kg -1 ) was the most abundant element, followed by calcium (1.15 g kg -1 ). (Canellas et al, 1992). Artificial sweeteners or sugar substitutes are organic materials used to sweeten food.…”
Section: Introductionmentioning
confidence: 99%